Analysis of Working Position Improvement to Minimize Musculoskeletal Disorder for Furniture Workers In UD. Jati Semi Dusun Sudimoro District of Nganjuk - Devina Rosa Hendarti; Zulfa Khalida (Universitas Trunojoyo Madura, 2019)
Musculoskeletal disorder is one of the risks due to improper working position. The most common problems in UD. Jati Semi were started from woodcutting up to finishing processes were the poor material arrangement, unergonomic working position, and dust from the wood cutting process. The risk assessment was performed by HIRA (Hazard Identification, Risk Assessment) method. The results showed that there were 4 risks in the accepted category, 1 risk in the moderate category, and 3 risks in the unaccepted category. The methods for analyzing working postures were performed by RULA (Rapid Upper Limb Assessment) and OWAS (Ovako Work Posture Analysis). The RULA results showed that the first installation and the cutting processes were classified as high-risk category, the second installation and the machine sanding processes were classified as the moderate-risk category, and the engraving by machine, the manual engraving, and the staining processes were classified as small-risk category. The OWAS results showed that the first installation, the sanding by machine, the engraving by machine, and the second installation processes were classified as the moderate category, the staining process was classified as quite category, the cutting process was classified as the highest category , and the engraving process was classified as the low category.